Pollution and biology in the coastal area of San Isidro, Miraflores, Barranco and Chorrillos - Rodenas Seytuque, Pedro José (2019)
The objective of the research was determine the degree of contamination by coastal solid waste that affects the marine bioecology of the beaches of San Isidro, Miraflores, Barranco and Chorrillos. The research is descriptive-explanatory, not experimental. The sample was composed of 150 bathers and visitors, and by the organisms that inhabit the beaches and breakwaters of San Isidro, Miraflores, Barranco and Chorrillos. The data have been classified in a contingency table to test the hypothesis, of independence of criteria, througth of the chi square. Considering a level of significance α = 0.05 and 1 degree of freedom whose tabular value is X2 (0.05, 1) = 3.8416, which was then compared with the experimental chi square to accept or reject the null hypothesis. The value reached of 14.60 for the experimental square chi that is higher than the tabular value (3.8416), which allows the null hypothesis to be rejected at a level of significance of 5%, so it is concluded that the contamination by solids waste that are found in the coastal area have a significant impact on the bioecology of the organisms that inhabit the beaches and breakwaters of San Isidro, Miraflores, Barranco and Chorrillos.